Manifestations des jeunes dans les villes africaines : déviance, délinquance ou violence politique - LIFOLI BALEA, Jean-Pierre; Omba, Jean Andriozi (IJRDO - Journal of Social Science and Humanities Research, 2019)
This paper is the result of an investigation led in the month of November 2018 in Kisangani in RDC, to understand the reasons that push the African youngsters in the south of the Sahara to protest violement against the political institutions. For these young, the violence is the only language that can oblige the political leaders of their countries to take into account their demands. However, if the violence at the time of the demonstrations of protest allows the African youngsters to pose their problems to the political authorities, the violence also exposes the young to the cardiac illnesses and to the mental depression.